A Morphological Study of the Evolution of Eight Organisms Through a Morphological Phylogeny - Sammer Marzouk (International Journal of Life Sciences, 2017)
Introduction: In this study, eight different shells from different species were examined by looking at the physical features of the shells. The purpose of the study was to identify evolutionary links between species with shells. From these physical features, a morphological phylogeny was compiled. And from the morphological phylogeny, it was shown that their the family of the shells was the first trait defined specific clades and that each synapomorphic trait after this was a physical feature of the shells. Results: From the experiment, the following conclusions were discovered: 1) That Scallops and Cockles are the most morphologic clay similar. 2) For taxa A, trait III is an apomorphy because this traits is a single traits that defines this taxa separately form the other taxa. 3) For taxa A, traits I is a plesiomorphy because it is a trait that is ancestral to trait III which defines taxa A. Conclusions: From the data, these conclusions could introduce a new topic, new ideas, and new information to existing researches. The influx of new ideas would either become helpful, or build off the research of other researchers. This would help the scientific community in increasing its knowledge of the evolutionary background of more species.